A case study about complete battery implementation onboard tugs - Höckersten, Andreas; Nilsson, Adam (My University, 2018)
New regulations are presented as a reaction to the shipping industry`s contribution to the global warming and emission of other pollutants. New sustainable solutions to energy production onboard ships are therefore needed. Battery power have been presented as one of the solution to lower dangerous emissions from burning fossil fuels in combustion engines. Fully electric cars powered by stored energy in batteries already exists and can be seen as an emission free solution. However, the concept is not common within the shipping industry, even if there is a rising interest in the subject. This paper is presenting that vessels with a fixed route such as ferries have showed the biggest interest in adapting this concept with battery. However, hybrid systems are more common in the shipping industry but could act as an important first step when going from diesel to battery. The purpose of this thesis is to investigate the environmental and economic benefits and disadvantages of converting a hybrid tugboat to a fully electric vessel, how much the local society, close to where the vessel operates have to gain on this retrofitting to a fully electric propulsion line and what the difference in cost between the hybrid propulsion line and the fully electric. The results are achieved with help of scientific literature and calculations with information from the company that owns the vessel we are investigating for this case study. The results of converting a hybrid vessel to a fully electric vessel with a battery energy storage system onboard shows that the benefits for the local area where the ship is operating, regarding costs for health issues related to harmful emissions of NOx (Nitrogen Oxides), SOx (Sulphur Oxides), PM (Particular Matter) and VOC (Volatile Organic Compound), are high. Considering the results when calculating the global effects on CO2 (Carbon dioxide) emissions, the same benefits with the energy system change is not as great since the result show a very little difference, depending in which country the electricity is produced in. Regarding the production of the li-ion (Lithium-Ion) batteries, the calculations are showing that only a fraction of the total CO2 emissions from the battery are coming from the production.
Keywords: Energi; Transport; Hållbar utveckling; Energisystem; Marin teknik; Energy; Transport; Sustainable Development; Energy Systems; Marine Engineering